Composite negative electrode graphite material and preparation method thereof, negative electrode sheet and lithium ion battery
By using composite negative electrode graphite materials in lithium-ion batteries, the particle size and mass ratio of particulate graphite and modified graphite is optimized, and the problem of reduced power performance of lithium-ion batteries in low-temperature environments is solved, and higher low-temperature performance and capacity are achieved.
Patent Information
- Application Number
- CN202411706030.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing lithium-ion batteries have reduced power performance and significantly reduced charging capacity in low-temperature environments, especially the low-temperature performance of lithium iron phosphate batteries is poor.
A composite negative electrode graphite material is used, which consists of granular graphite and modified graphite. The modified graphite includes graphite particles and a cladding layer coated on the surface of graphite particles. By optimizing the D50 particle size and mass ratio of the particle graphite and modified graphite, the particle size of the negative electrode graphite material is reduced, the lithium ion diffusion rate is improved, and the charge transfer resistance and polarization are reduced through surface coating.
The low-temperature performance of lithium-ion batteries is improved, making the discharge time at low temperatures longer and the capacity is higher, while maintaining good cycle stability.
Smart Images

Figure CN119764364A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite negative electrode graphite material and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, and high output voltage, and are widely used in consumer electronics, electric vehicles, and energy storage. However, when lithium-ion batteries are operated in low-temperature environments, they have problems such as reduced power performance and significantly reduced charge capacity, which seriously restricts their use.
[0003] At present, research on the failure mechanism of positive electrodes at low temperatures is relatively limited, and the academic community generally believes that positive electrode materials are not the key factor in the low-temperature failure of lithium-ion batteries. Summary of the invention
[0004] The main purpose of the present invention is to provide a composite negative electrode graphite material and a preparation method thereof, a negative electrode sheet and a lithium ion battery, so as to solve the problem of poor low temperature performance of lithium iron phosphate batteries in the prior art.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a composite negative electrode graphite material is provided, which includes particulate graphite and modified graphite, the modified graphite includes graphite particles and a coating layer coated on the surface of the graphite particles, the D50 particle size of the particulate graphite is 8 to 10 μm; the D50 particle size of the modified graphite is 12 to 14 μm.
[0006] Furthermore, the mass ratio of the above-mentioned granular graphite to modified graphite is 80-99:1-20.
[0007] Furthermore, the mass ratio of the above-mentioned granular graphite to modified graphite is 90-99:1-10.
[0008] Furthermore, the mass proportion of the coating layer in the above-mentioned modified graphite is 2.9-3.4%.
[0009] Furthermore, the D50 particle size of the composite negative electrode graphite material is 10 to 12 μm.
[0010] According to another aspect of the present invention, a method for preparing the aforementioned composite negative electrode graphite material is provided, and the preparation method comprises: step S1, coating a carbon source precursor containing heteroatoms on the surface of graphite particles to obtain coated graphite particles; step S2, mixing raw materials including coated graphite particles and particulate graphite to obtain a mixture; step S3, carbonizing the mixture to obtain a composite negative electrode graphite material.
[0011] Furthermore, in the above step S1, the carbon source precursor is selected from any one or more of asphalt, resin and petroleum coke; and / or the mass ratio of the carbon source precursor to the graphite particles is 5 to 6:100.
[0012] Furthermore, in the above step S3, the temperature of the carbonization treatment is 1100-1300°C, and / or the time of the carbonization treatment is 2-5 hours. According to another aspect of the present invention, a negative electrode sheet is provided, comprising a negative electrode material, the negative electrode material is the above-mentioned composite negative electrode graphite material, or the negative electrode material is prepared by the above-mentioned preparation method.
[0013] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a lithium iron phosphate positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.
[0014] Applying the technical solution of the present invention, the composite negative electrode graphite material of the present application includes granular graphite and modified graphite. Compared with the current mainstream negative electrode graphite of lithium iron phosphate battery, by optimizing the D50 particle size of granular graphite and modified graphite, the composite negative electrode graphite material of the present application reduces the particle size of the negative electrode graphite material, the corresponding lithium ion diffusion path is shorter, the diffusion coefficient is larger, and the battery voltage reduction amplitude is reduced, so that the composite negative electrode graphite material needs a longer time to reach the lower limit cut-off voltage before reaching its available capacity, so that the discharge time of the composite negative electrode graphite material at low temperature becomes longer, and then the capacity of the composite negative electrode graphite material will be higher. Modified graphite includes graphite particles and a coating layer coated on the surface of the graphite particles. On the one hand, the charge transfer resistance between graphite and the electrolyte can be reduced by surface coating, and the diffusion rate of lithium ions between graphite layers can be increased, thereby increasing the embedding speed of lithium ions on the surface of negative electrode graphite particles, reducing the occurrence of lithium precipitation, and improving the low temperature performance of lithium ion batteries. On the other hand, surface coating can reduce the polarization caused by the large lithium ion concentration difference, reduce lithium dendrites, and reduce the loss of active lithium and the accumulation of by-products caused by the irreversible reaction between highly active metallic lithium and the electrolyte, thereby improving the low-temperature performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0016] Figure 1 A SEM image of a composite negative electrode graphite material provided according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0018] As analyzed in the background technology, the prior art has the problem that the low-temperature performance of lithium iron phosphate batteries is poor. To solve this problem, the present invention provides a composite negative electrode graphite material and a preparation method thereof, a negative electrode sheet and a lithium ion battery.
[0019] In a typical embodiment of the present application, a composite negative electrode graphite material is provided, which includes particulate graphite and modified graphite, the modified graphite includes graphite particles and a coating layer coated on the surface of the graphite particles, the D50 particle size of the particulate graphite is 8 to 10 μm; the D50 particle size of the modified graphite is 12 to 14 μm.
[0020] The composite negative electrode graphite material of the present application includes granular graphite and modified graphite. Compared with the current mainstream negative electrode graphite of lithium iron phosphate battery, by optimizing the D50 particle size of granular graphite and modified graphite, the composite negative electrode graphite material of the present application reduces the particle size of the negative electrode graphite material, the corresponding lithium ion diffusion path is shorter, the diffusion coefficient is larger, and the battery voltage reduction amplitude is reduced, so that the composite negative electrode graphite material needs a longer time to reach the lower limit cut-off voltage before reaching its available capacity, so that the discharge time of the composite negative electrode graphite material at low temperature becomes longer, and then the capacity of the composite negative electrode graphite material will be higher. Modified graphite includes graphite particles and a coating layer coated on the surface of the graphite particles. On the one hand, the charge transfer resistance between graphite and the electrolyte can be reduced by surface coating, and the diffusion rate of lithium ions between graphite layers can be increased, thereby increasing the embedding speed of lithium ions on the surface of negative electrode graphite particles, reducing the occurrence of lithium precipitation, and improving the low temperature performance of lithium ion batteries. On the other hand, surface coating can reduce the polarization caused by the large lithium ion concentration difference, reduce lithium dendrites, and reduce the loss of active lithium and the accumulation of by-products caused by the irreversible reaction between highly active metallic lithium and the electrolyte, thereby improving the low-temperature performance of the battery.
[0021] In one embodiment of the present application, the mass ratio of the above-mentioned granular graphite to modified graphite is 80-99:1-20.
[0022] By controlling the mass ratio of particulate graphite and modified graphite within the above range, it is beneficial to improve the low-temperature performance of the battery while maintaining good cycle stability.
[0023] In order to further take into account the low temperature performance and cycle stability of the battery, in one embodiment of the present application, the mass ratio of the above-mentioned particulate graphite and modified graphite is preferably 90-99:1-10.
[0024] In one embodiment of the present application, the mass ratio of graphite particles to coating layers in the modified graphite is 90-95:5-10.
[0025] By controlling the mass ratio of graphite particles and coating layer within the above range, on the one hand, it helps to improve the structural stability of graphite particles and maximize the proportion of active materials, thereby increasing the energy density of the battery. On the other hand, the appropriate mass ratio can ensure that the coating layer is not too thick, thereby avoiding increasing the internal resistance of the battery and affecting the penetration of the electrolyte and the diffusion of lithium ions.
[0026] In one embodiment of the present application, the D50 particle size of the composite negative electrode graphite material is 10 to 12 μm.
[0027] By controlling the D50 particle size of the granular graphite to 8-10 μm and the D50 particle size of the modified graphite to 12-14 μm, the D50 particle size of the composite negative electrode graphite material of the present application is 10-12 μm. Compared with the current mainstream negative electrode graphite of lithium iron phosphate batteries, the composite negative electrode graphite material with a D50 particle size of 10-12 μm reduces the particle size of the negative electrode active material, the corresponding lithium ion diffusion path is shorter, the diffusion coefficient is large, the battery voltage reduction is lower, and it takes a longer time for the graphite to reach the lower limit cut-off voltage before reaching its available capacity. The discharge time is long at low temperature, and the available capacity will be higher.
[0028] In another typical embodiment of the present application, a method for preparing a composite negative electrode graphite material is provided, and the preparation method comprises: step S1, coating a carbon source precursor containing heteroatoms on the surface of graphite particles to obtain coated graphite particles; step S2, mixing raw materials including coated graphite particles and particulate graphite to obtain a mixture; step S3, carbonizing the mixture to obtain a composite negative electrode graphite material.
[0029] The above preparation method is to coat the surface of graphite particles with a carbon source precursor to obtain coated graphite particles, and to carbonize the mixture including the coated graphite particles and the granular graphite so that the carbon source precursor is carbonized on the surface of the graphite particles to form a coating layer, thereby obtaining a composite negative electrode graphite material. While reducing lithium dendrites, the composite negative electrode graphite material can also reduce the loss of active lithium and the accumulation of by-products caused by the irreversible reaction of highly active metallic lithium and the electrolyte, thereby improving the low temperature performance of the battery. The above preparation method is simple and low in cost.
[0030] In addition, the carbon source precursor containing heteroatoms can be coated on the surface of graphite particles by a coating method combining solid phase and liquid phase to obtain coated graphite particles.
[0031] In one embodiment of the present application, in the above step S1, the carbon source precursor is selected from any one or more of asphalt, resin and petroleum coke; and / or the mass ratio of the carbon source precursor to the graphite particles is 5 to 6:100.
[0032] The types of carbon source precursors are preferably within the above range, which helps to enrich the types of raw material choices for the carbon source precursors. Asphalt is usually used to prepare carbon materials with a high degree of graphitization, and resin materials have high specific surface area and pore volume, which are suitable for preparing porous carbon materials with a specific pore structure. The mass ratio of the carbon source precursor to the graphite particles is preferably controlled within the above range, which helps to improve the structural stability of the graphite particles while maximizing the proportion of active substances, thereby increasing the energy density of the battery. At the same time, the above types of carbon source precursors contain a certain amount of heteroatoms. After carbonization treatment, the heteroatoms are still retained in the coating layer, which helps to improve the overall contact effect between the composite negative electrode graphite material and the electrolyte.
[0033] In order to promote the formation of a coating layer on the surface of the graphite particles, in one embodiment of the present application, it is preferred that the temperature of the carbonization treatment is 1100-1300° C., and / or the time of the carbonization treatment is 2-5 hours.
[0034] In another typical embodiment of the present application, a negative electrode sheet is provided, comprising a negative electrode material, wherein the negative electrode material is the aforementioned composite negative electrode graphite material, and the negative electrode material is prepared by the aforementioned method for preparing the composite negative electrode graphite material.
[0035] The negative electrode sheet including the composite negative electrode graphite material of the present application has higher cycle performance and low temperature performance.
[0036] In another typical embodiment of the present application, a lithium-ion battery is provided, including a lithium iron phosphate positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet mentioned above.
[0037] Since the above-mentioned negative electrode sheet is the negative electrode sheet of the present application, the lithium-ion battery has a higher energy density and a longer cycle life, and the lithium-ion battery also has a higher low-temperature performance.
[0038] The beneficial technical effects of the present application will be described below in combination with specific embodiments and comparative examples.
[0039] Example 1
[0040] 5 g of asphalt was mixed with 100 g of graphite particles with a D50 particle size of 8 μm, and then carbonized to obtain coated graphite particles with a D50 particle size of 14 μm; the coated graphite particles were mixed with the raw materials of particulate graphite with a D50 particle size of 8 μm, and then carbonized at 1200° C. The carbonization time was 3 hours to obtain a composite negative electrode graphite material, wherein the mass ratio of the coated graphite particles to the particulate graphite was 10:90, and the mass proportion of the coating layer in the modified graphite was 2.9%. The SEM image of the composite negative electrode graphite material is as follows: Figure 1 shown.
[0041] Example 2
[0042] The difference from Example 1 is that the mass ratio of coated graphite particles to particle graphite is 1:99, and a composite negative electrode graphite material is finally obtained.
[0043] Example 3
[0044] The difference from Example 1 is that the mass ratio of coated graphite particles to particle graphite is 20:80, and a composite negative electrode graphite material is finally obtained.
[0045] Example 4
[0046] The difference from Example 1 is that the mass ratio of coated graphite particles to particle graphite is 5:95, and a composite negative electrode graphite material is finally obtained.
[0047] Example 5
[0048] The difference from Example 1 is that the mass ratio of coated graphite particles to particle graphite is 25:75, and a composite negative electrode graphite material is finally obtained.
[0049] Example 6
[0050] The difference from Example 1 is that the mass ratio of coated graphite particles to particulate graphite is 0.5:99.5, and a composite negative electrode graphite material is finally obtained.
[0051] Example 7
[0052] The difference from Example 1 is that the mass ratio of asphalt to graphite particles is 6:100, the mass proportion of the coating layer in the modified graphite is 3.4%, and finally a composite negative electrode graphite material is obtained.
[0053] Example 8
[0054] The difference from Example 1 is that the mass ratio of asphalt to graphite particles is 6.5:100, the mass proportion of the coating layer in the modified graphite is 3.8%, and finally a composite negative electrode graphite material is obtained.
[0055] Example 9
[0056] The difference from Example 1 is that the carbon source precursor is petroleum coke, and a composite negative electrode graphite material is finally obtained.
[0057] Example 10
[0058] The difference from Example 1 is that the temperature of the carbonization treatment is 1300° C., and a composite negative electrode graphite material is finally obtained.
[0059] Embodiment 11
[0060] The difference from Example 1 is that the temperature of the carbonization treatment is 1000° C., and a composite negative electrode graphite material is finally obtained.
[0061] Comparative Example 1
[0062] The difference from Example 1 is that the composite negative electrode graphite material is entirely composed of granular graphite with a D50 particle size of 8 to 10 μm.
[0063] Comparative Example 2
[0064] The difference from Example 1 is that the D50 particle size of the granular graphite is 14-16 μm, and the D50 particle size of the coated graphite particles is 15-16 μm, and finally a composite negative electrode graphite material is obtained.
[0065] The positive electrode is made of lithium iron phosphate LFP material, and the negative electrode is made of the composite negative electrode graphite material obtained in the above embodiments and comparative examples. The positive electrode sheet is composed of LFP, polyvinylidene fluoride PVDF, and conductive carbon black SP. The negative electrode sheet is composed of the composite negative electrode graphite material obtained in the above embodiments and comparative examples, conductive carbon black SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR. The diaphragm uses a 16μm PP base film. The electrolyte contains 1mol / L LiPF6, the solvent is EC:EMC:DEC (mass ratio 25:40:30) and 2wt% VC. The negative electrode sheet, diaphragm and positive electrode sheet are stacked in a Z shape to make a soft-pack battery. The designed N / P is 1.15 and the designed capacity is 3Ah.
[0066] Test standard:
[0067] Charge with the standard charging method (0.5C), leave for 30 minutes, discharge with the standard discharge method (0.5C), and cycle 3 times as the initial step.
[0068] The cells were charged to 3.65V at 0.5C constant current and constant voltage, and then placed at 0℃, -10℃, and -20℃ for 24h.
[0069] At -20℃, discharge at 0.2C constant current to 2.0V.
[0070] At -20℃, charge and discharge at 1C constant current for 1000 times.
[0071] The above test results are listed in Table 1.
[0072] Table 1
[0073]
[0074] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0075] The composite negative electrode graphite material of the present application includes granular graphite and modified graphite. Compared with the current mainstream negative electrode graphite of lithium iron phosphate battery, by optimizing the D50 particle size of granular graphite and modified graphite, the composite negative electrode graphite material of the present application reduces the particle size of the negative electrode graphite material, the corresponding lithium ion diffusion path is shorter, the diffusion coefficient is larger, and the battery voltage reduction amplitude is reduced, so that the composite negative electrode graphite material needs a longer time to reach the lower limit cut-off voltage before reaching its available capacity, so that the discharge time of the composite negative electrode graphite material at low temperature becomes longer, and then the capacity of the composite negative electrode graphite material will be higher. Modified graphite includes graphite particles and a coating layer coated on the surface of the graphite particles. On the one hand, the charge transfer resistance between graphite and the electrolyte can be reduced by surface coating, and the diffusion rate of lithium ions between graphite layers can be increased, thereby increasing the embedding speed of lithium ions on the surface of negative electrode graphite particles, reducing the occurrence of lithium precipitation, and improving the low temperature performance of lithium ion batteries. On the other hand, surface coating can reduce the polarization caused by the large lithium ion concentration difference, reduce lithium dendrites, and reduce the loss of active lithium and the accumulation of by-products caused by the irreversible reaction between highly active metallic lithium and the electrolyte, thereby improving the low-temperature performance of the battery.
[0076] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite negative electrode graphite material, characterized in that: The composite negative electrode graphite material includes granular graphite and modified graphite, wherein the modified graphite includes graphite particles and a coating layer coated on the surface of the graphite particles, the D50 particle size of the granular graphite is 8 to 10 μm; and the D50 particle size of the modified graphite is 12 to 14 μm.
2. The composite negative electrode graphite material according to claim 1, characterized in that: The mass ratio of the particle graphite to the modified graphite is 80-99:1-20.
3. The composite negative electrode graphite material according to claim 2, characterized in that: The mass ratio of the particle graphite to the modified graphite is 90-99:1-10.
4. The composite negative electrode graphite material according to any one of claims 1 to 3, characterized in that: The mass proportion of the coating layer in the modified graphite is 2.9-3.4%.
5. The composite negative electrode graphite material according to any one of claims 1 to 4, characterized in that: The D50 particle size of the composite negative electrode graphite material is 10 to 12 μm.
6. A method for preparing the composite negative electrode graphite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step S1, coating the surface of graphite particles with a carbon source precursor containing heteroatoms to obtain coated graphite particles; Step S2, mixing the raw materials including the coated graphite particles and the granular graphite to obtain a mixture; Step S3, carbonizing the mixture to obtain a composite negative electrode graphite material.
7. The preparation method according to claim 6, characterized in that: In the step S1, the carbon source precursor is selected from any one or more of asphalt, resin and petroleum coke; and / or the mass ratio of the carbon source precursor to the graphite particles is 5 to 6:
100.
8. The preparation method according to claim 6 or 7, characterized in that: In the step S3, the temperature of the carbonization treatment is 1100-1300° C., and / or the time of the carbonization treatment is 2-5 hours.
9. A negative electrode sheet, comprising a negative electrode material, characterized in that: The negative electrode material is the composite negative electrode graphite material according to any one of claims 1 to 5, or the negative electrode material is prepared by the preparation method according to any one of claims 6 to 8.
10. A lithium ion battery comprising a lithium iron phosphate positive electrode sheet and a negative electrode sheet, characterized in that: The negative electrode sheet is the negative electrode sheet according to claim 9.